Analisis strategi bauran pemasaran dalam upaya menarik tamu di santan restaurant hotel horison ultima timika papua - Ratulohain, Julvin; Sulistyawati, Agung Sri; Sutaguna, I Nyoman Tri (Jurnal Kepariwisataan dan Hospitalitas; Vol 8 No 1 (2024): Vol.8,No.1,2024, 2024)
The crisis caused by COVID-19 has decreased tourist visits to Santan Restaurant, therefore it is necessary to conduct research on marketing mix strategies in order to attract guest at Santan Restaurant. The sample of this study were 79 visitors who had tried food and beverages at Santan Restaurant. Data were collected in several ways, such as: observation, interviews, questionnaires, documentation, and literature study. Data was analysed by SWOT analysis. The results showed that from 20 indicators of internal factor, 13 indicators were categorized as strengths, while the other 7 indicators were categorized as weaknesses. Meanwhile, from 8 indicators of external factor, 3 indicators are categorized as opportunities and 5 indicators are categorized as threats. Based on the results of the SWOT analysis, several strategies recommended to Santan Restaurant such as: (1) collaborate with the government, (2) make special package for gathering, (3) conducting employee training, (4) rearranging interior design, (5) regularly post on social media, (6) collaborate with influencers, (7) make promo, (8) focus on online sales, and (9) add facilities to be able to compete with competitors.     Keywords : Strategies, Marketing Mix, Santan Restaurant.     The crisis caused by COVID-19 has decreased tourist visits to Santan Restaurant, therefore it is necessary to conduct research on marketing mix strategies in order to attract guest at Santan Restaurant. The sample of this study were 79 visitors who had tried food and beverages at Santan Restaurant. Data were collected in several ways, such as: observation, interviews, questionnaires, documentation, and literature study. Data was analysed by SWOT analysis. The results showed that from 20 indicators of internal factor, 13 indicators were categorized as strengths, while the other 7 indicators were categorized as weaknesses. Meanwhile, from 8 indicators of external factor, 3 indicators are categorized as opportunities and 5 indicators are categorized as threats. Based on the results of the SWOT analysis, several strategies recommended to Santan Restaurant such as: (1) collaborate with the government, (2) make special package for gathering, (3) conducting employee training, (4) rearranging interior design, (5) regularly post on social media, (6) collaborate with influencers, (7) make promo, (8) focus on online sales, and (9) add facilities to be able to compete with competitors. Keywords : Strategies, Marketing Mix, Santan Restaurant.